1994
DOI: 10.1007/bf00428782
|View full text |Cite
|
Sign up to set email alerts
|

Expression of glycogen synthase and phosphofructokinase in muscle from Type 1 (insulin-dependent) diabetic patients before and after intensive insulin treatment

Abstract: SummaryThe aim of the present study was to determine whether short-term appropriate insulinization of Type i (insulin-dependent) diabetic patients in longterm poor glycaemic control (HbAlc > 9.5 %) was associated with an adaptive regulation of the activity and gene expression of key proteins in muscle glycogen storage and glycolysis: glycogen synthase and phosphofructokinase, respectively. In nine diabetic patients biopsies of quadriceps muscle were taken before and 24-h after intensified insulin therapy and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…The absence of alterations of GS and PFK-1 mRNAs in the presence of physiological levels of hyperinsulinemia has already been reported (8,10,11). The lack of change in the presence of high insulin concentrations suggests that the expression of these genes is not regulated by insulin.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The absence of alterations of GS and PFK-1 mRNAs in the presence of physiological levels of hyperinsulinemia has already been reported (8,10,11). The lack of change in the presence of high insulin concentrations suggests that the expression of these genes is not regulated by insulin.…”
Section: Discussionmentioning
confidence: 61%
“…The expression of the protein Ras associated to diabetes (Rad) 1 was enhanced (6) and the expression of hexokinase II (7) and glycogen synthase (GS) (8) was decreased in patients with non-insulindependent diabetes mellitus (NIDDM). On the other hand, the expression of the genes coding Glut 4 (9) and 6-phosphofructo-1-kinase (PFK-1) (8) seemed unaltered in obese or NIDDM patients, and intensive insulin treatment did not modify the expression of the genes for GS and PFK-1 in type I diabetic subjects (10). Using the euglycemic hyperinsulinic glucose clamp, a method that allows the individual effect of insulin to be studied, it was found that Glut 4, GS, and hexokinase I mRNA levels were unaltered in normal muscle; whereas, hexokinase II mRNA increased three times in response to insulin (11).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies of diabetic muscle properties have typically selected patients without carefully screening for activity (23,42) or included active patients with "no more than two exercise sessions weekly on a regular basis" (19). We chose to closely match patients to control subjects to eliminate any bias due to activity and used a sample size similar to that in other studies of muscle properties in types 1 and 2 patients (42,45,47). This matching permitted us to take into account the role of chronic activity level in the variation in the energetic properties of a muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Assays of a key glycolytic enzyme, phosphofructokinase, showed no difference between type 1 diabetic patients and control subjects (45). However, measurements during exercise provide evidence that the lower oxidative and higher glycolytic fluxes found in obesity and type 2 diabetes are also common to type 1 diabetes; specifically, V O 2 max is reduced (34) and blood lactate levels are elevated (48) in exercising type 1 patients compared with age-and activity-matched control subjects.…”
mentioning
confidence: 93%
“…Defects in this enzyme can significantly alter the intracellular routing and metabolism of glucose and contribute to insulin resistance in muscle tissue. Individuals with obesity and those with type II and type I diabetes and in poor metabolic control often exhibit insulin resistance (4,5) that is associated with impaired GS activity and reduced rates of glycogen synthesis in skeletal muscle (2,(5)(6)(7)(8)(9)(10)(11)(12). While these abnormalities may have an underlying genetic basis in obesity and type II diabetes (13,14), recent evidence indicates that there are likely to be acquired components of insulin resistance in these conditions as well (15,16).…”
mentioning
confidence: 99%